Influence of jaw gape on EMG of jaw muscles and jaw-stretch reflexes - Wang, Kelun; Lobbezoo, Frank; Svensson, Peter; Arendt-Nielsen, Lars (Archives of oral biology, 2007)
The influence of jaw gapes on jaw-stretch reflexes and jaw muscles activity was studied in order to test the sensitivity of human muscle spindle afferents in various jaw muscles. Twelve healthy men (mean age ± S.E.M.: 25.0 ± 1.2 yr) participated in the study. Short-latency excitatory reflex responses were evoked by a custom-made stretch device with the subjects biting on a jaw-bar with their front teeth. Surface electromyographic (sEMG) recordings from right masseter (MAR), and right temporalis (TAR), intramuscular EMG (imEMG) recordings from right lateral pterygoid (LPR) and right anterior digastric (ADR) muscles were made. The reflex at different jaw gapes of 6, 10, 14, 18, 22, 26, 30, 34, and 38 mm were examined in random order with standard stretch conditions of 1 mm displacement and 10 ms ramp time. Twenty sweeps of the reflex were recorded at each level with at least 5 s interval between each sweep with online monitoring of the visual feed back at 15% of maximum voluntary contraction (MVC) of each jaw gape from MAR. The results showed that the peak-to-peak amplitude of the jaw-stretch reflex in MAR was significantly higher at 14 mm compared to 30, 34, and 38 mm ( P < 0.038), whereas the reflex amplitude in TAR increased with jaw gape until a maximum at 34 mm. There was no significant effect of jaw gape in LPR muscles ( P = 0.825) and no obvious stretch reflex was observed in ADR. When the amplitude was normalised to the pre-stimulus EMG at each jaw gape, the highest normalised amplitude was observed at 14 mm jaw gape in MAR, however there was no significant effect of jaw gape on the normalised amplitude in TAR and LPR. In addition, masseter EMG at MVC significantly decreased with the increase of the gapes, i.e. biting at 6, 14, and 18 mm gapes had a significantly higher MVC compared to 26, 30, 34, and 38 mm (ANOVA: P < 0.013). It is concluded that the jaw gapes influence the sensitivity of the human muscle spindle afferents in jaw-closing muscles with a distinct peak, which is within normal jaw gapes during function.